1980
DOI: 10.1152/ajpheart.1980.239.4.h450
|View full text |Cite
|
Sign up to set email alerts
|

Effects of estradiol on release and disposition of norepinephrine from nerve endings

Abstract: Studies were performed to determine whether estradiol (E2) has a direct action on the release and disposition of norepinephrine (NE) from adrenergic nerve endings in isolated superfused canine saphenous veins. [3H]NE and is labeled metabolites were separated by column chromatography with measurement by liquid scintillation spectrometry. An increase in the spontaneous overflow of total 3H, [3H]NE, and [3H]dihydroxyphenylglycol ([3H]DOPEG) that occurred with 1 and 10 microgram/ml E2 in the superfusing medium sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

1982
1982
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…25 Additionally, estrogen may affect both vasodilation and vasoconstriction by increasing adrenergic activity. 26,27 The diameter enlargement observed in the current study may also signal a compensatory response to alterations in sheer stress levels resulting from adverse stimuli such as increased blood pressure or enhanced wall thickening. 28,29 CCA adventitial diameters were significantly larger among late perimenopausal and postmenopausal women and with lower estradiol levels, while CCA IMT values showed no association with menopause status or sex hormones after adjustment for chronological age.…”
Section: Discussionmentioning
confidence: 69%
“…25 Additionally, estrogen may affect both vasodilation and vasoconstriction by increasing adrenergic activity. 26,27 The diameter enlargement observed in the current study may also signal a compensatory response to alterations in sheer stress levels resulting from adverse stimuli such as increased blood pressure or enhanced wall thickening. 28,29 CCA adventitial diameters were significantly larger among late perimenopausal and postmenopausal women and with lower estradiol levels, while CCA IMT values showed no association with menopause status or sex hormones after adjustment for chronological age.…”
Section: Discussionmentioning
confidence: 69%
“…With respect to the high level of CPP observed in the female group, it is known that estrogen may have indirect effects on the cardiovascular system, e.g., through an interaction with the adrenergic nervous system (28). Many studies have indicated a synergistic effect with sympathetic activity through inhibition of norepinephrine uptake (29), leading to an increase in vascular tonus. An increase in reactivity to norepinephrine has also been shown in oophorectomized (30) and prepuberal rats (23) treated with estrogen.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in estrogen levels would result in enhanced epinephrine excretion, because estradiol is able to increase adrenal tyrosine hydroxylase activity in adult rats (Kohier et al, 1975) and to enhance non stimulated epinephrine release from bovine adrenal medulla (Wiecbrnan and Borowitz, 1979). On the other hand, estradiol is known to inhibit neuronal and extraneuronal uptake of catecholamines (Hamlet et al, 1980) and to decrease catechol-O-methyltransferase activity in human liver (Bail et al, 1972;Cohn and Axelrod, 1971). Although unaltered or increased COMT activity has been found in some tissues after estradiol administration (Cohn and Axelrod, 1971;Scardapane and Cardinali, 1977;Wurtman et al, 1964) it seems likely that liver COMT plays the predominant rote to inactivate blood epinephrine in human.…”
Section: Discussionmentioning
confidence: 99%